Learning Motivation as a Mediator of Curriculum Relevance and Seedling Understanding on Practical Readiness in Forestry Education - Hadi, Wirawan Noor; Basir, Basir; Fitriani, Adistina (Fakultas Kehutanan Universitas Mulawarman, 2026)
The challenge for forestry education is both the transfer of technical knowledge and whether students are adequately prepared to practice in the field. We examined the relationships among the four variables: Seedling Understanding (SU), Curriculum Relevance (CR), Learning Motivation (LM) and Practical Readiness (PR) among forestry undergraduates. We employed a quantitative, explanatory design based on data from 54 students taking a Seedling Techniques course. PLS-SEM was used for measuring and structural models testing. Results show that curriculum relevance (β = 0.487) and seedling understanding (β = 0.349) significantly increase learning motivation, which strongly predicts practical readiness (β = 0.627; R² = 0.798). These findings highlight the importance of motivation-driven curriculum design to enhance practice-ready forestry graduates. These results imply that technical understanding and curriculum design are necessary but only lead to readiness because of their motivational impact on students use or integration of those skills; using lessons learned to motivate student engagement and further application of practical knowledge. This integration of cognitive, pedagogical, and motivational dimensions into a single empirical model is a unique aspect of the study and extends the motivational theory currently present in the literature to include forestry education. In practical terms, the results provide some suggestions on the development of curricula and teaching strategies that incorporate relevance, autonomy and practice to develop competence and preparedness.